Epilithic Diatom Assemblages and Indicators for the Assessment of Water Quality of Munzur Stream, Turkey - Kaplan, İmdat; Yıldırım, Vesile (Uğur ÇAKILCIOĞLU, 2023)
The epilithic diatoms of Munzur Stream, together with the chemistry and physical variables of the water, were examined in the samples taken annually from 3 stations on the creek between October 2016 and September 2017. A total of 69 diatom taxa were identified benthic habitat. Cocconeis placentula, Cymbella affinis, Cymbella excisiformis , Didymosphenia geminata, Gomphonema olivaceum, and Hannaea arcus became diatoms at all that reached significant relative abundance. Shannon-diversity (H’), species evenness (J’), species richness (S) in each station varied between stations and months. Regarding diversity (H), values ranged from 1.54 (in December, at S3) to 2.99 (in October, at S3). Evenness ranged from 0.09 to 0.22 at station S3 in September (at S1, in September). Evenness ranged from 0.09 at site S3 in September, to 0.22 at S1, in September. All stations and species were close to 1 value. Canonical correspondence analysis indicated that three environmental variables (TN,TP, PO4-3) significantly affected the distribution of epilithic diatom. The studied part of stream was characterized by the species susceptible to nutrients such as Didymosphenia geminata, Cymbella excisiformis and Hannaea arcus which are found in the regions located in high lands having advanced ecological status. The results of the present study highlighted the importance of diatoms as a bio-indicator for health condition of a stream.
Keywords: Botany (Other); Bitki Bilimi (Diğer)